Tracing Islamic Civilization in Eastern Nusantara: Archaeological Evidence and Cultural Transformation in Patipi and Wertuer, Fakfak - Sukandar, Sri Chiirullia; Suryaningsi, Tini; Ansaar (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study traces the development of Islamic civilization in the eastern Indonesian archipelago through archaeological evidence and cultural transformation in Patipi and Wertuer, Fakfak, West Papua. The objective of the study is to identify material remains related to Islamic influence and analyze the integration of Islamic values into the local socio-cultural structure. The method used is a descriptive archaeological survey based on literature review, field observation, documentation, and interviews with key informants. The main findings include the Old Patimburak Mosque (circa 1870) as a center of worship and a symbol of religious authority, the north-south oriented royal tombs in accordance with Islamic burial traditions, and 72 ceramic fragments from the Ming Dynasty of the 15th-16th centuries, the Qing Dynasty of the 17th-20th centuries, and Europe of the 19th-20th centuries, which indicate the intensity of maritime trade networks. This data shows Fakfak's connection to the trade and missionary routes of the Maluku Sultanate, particularly Tidore, in the context of maritime political and economic expansion. The traditions of Mandi Syafar, Maulid Nabi, and religious practices during Ramadan reflect the ongoing process of acculturation between Islamic teachings and local traditions. It can be concluded that Islamic civilization in Fakfak developed through maritime connectivity, inter-sultanate political networks, and cultural adaptation, making this region an integral part of the history of Islam in eastern Indonesia.